Active osseointegration in an ex vivo porcine bone model - Hall, Thomas A. G.; Theodoridis, Konstantinos; Kohli, Nupur; Cegla, Frederic; van Arkel, Richard J. (Frontiers in Bioengineering and Biotechnology, 2024)
Achieving osseointegration is a fundamental requirement for many orthopaedic, oral, and craniofacial implants. Osseointegration typically takes three to six months, during which time implants are at risk of loosening. The aim of this study was to investigate whether osseointegration could be actively enhanced by delivering controllable electromechanical stimuli to the periprosthetic bone. First, the osteoconductivity of the implant surface was confirmed using an in vitro culture with murine preosteoblasts. The effects of active treatment on osseointegration were then investigated in a 21-day ex vivo model with freshly harvested cancellous bone cylinders (n = 24; Ø10 mm x 5 mm) from distal porcine femora, with comparisons to specimens treated by a distant ultrasound source and static controls. Cell viability, proliferation and distribution was evident throughout culture. Superior ongrowth of tissue onto the titanium discs during culture was observed in the actively stimulated specimens, with evidence of ten-times increased mineralisation after 7 and 14 days of culture (p < 0.05) and 2.5 times increased expression of osteopontin (p < 0.005), an adhesive protein, at 21 days. Moreover, histological analyses revealed increased bone remodelling at the implant-bone interface in the actively stimulated specimens compared to the passive controls. Active osseointegration is an exciting new approach for accelerating bone growth into and around implants.